Consumer‐driven nutrient dynamics in freshwater ecosystems: an introduction. (14th January 2015) - Capps, Krista A.; Atkinson, Carla L.; Rugenski, Amanda T.
Summary Over the past decade, studies of the effects of consumer‐driven nutrient dynamics have become more common. This work has demonstrated that animals can function as sources and sinks of elements, but few studies have broadly compared these processes among organisms and across ecosystems. Collectively, the articles in this special issue elucidate the important roles that organisms can play in nutrient dynamics in lotic, lentic and wetland ecosystems. These papers show how species‐specific traits, such as body stoichiometry and trophic ecology, and abiotic variables, including ambient water chemistry, govern the net impacts of consumer‐driven nutrient dynamics in freshwater ecosystems. Globally, the introduction of non‐native species and the loss of native biodiversity compromise the functional integrity of freshwater ecosystems. The work featured in this issue will help ecologists and conservation biologists integrate species‐specific traits with ecosystem‐specific conditions to understand the potential effects of changing biodiversity on ecosystem function in fresh waters.